The role of β-cyclodextrin in mediating regioselective dimethylaminomethylation of phenol. Issue 2 (11th January 2018) - Wu, Wen-Hai; Duan, Jiang; Wei, Ting; Tu, Hai-Yang; Zhang, Ai-Dong
Abstract: Regioselective reactions with supramolecular control are of great interest. Herein, the para -regioselectivity in the Mannich reaction of phenol with formaldehyde and dimethylamine was achieved with the use of β-cyclodextrin (β-CD), giving 4-( N, N -dimethylaminomethyl)phenol ( p -AP) as major product. 1 H NMR and ITC measurements of the binding of β-CD with the reactants and the products o - and p -AP revealed a new mechanism, in which β-CD includes p -AP instead of phenol to control the reaction regioselectivity. This product-inclusion mechanism is remarkably different to the known reactant-inclusion process. Graphical abstract: